Ultima Ratio and the Judicial Application of Law - Joxerramon Bengoetxea (Oñati Socio-Legal Series)
The nature of Ultima Ratio as a principle, its relationship to other principles in the criminal law is the first subject of this paper. After discarding approaches that deny any role to the ultima ratio principle like the criminal law of the enemy, the major readings of the justification of the ius puniendi – deontological and utilitarian – are related to the idea of a restrained resort to criminalisation and penal sanction. The role of the main protagonists in relation to punishment is next considered: transgressor, community and victim. The issues of impunity and overpunity are also considered in this part. The second part of the paper analyses the possible effects of ultima ratio, a general politico-moral principle mainly addressed to the legislator, on the application of the law by the judges. It is then turned into something closer to a general legal principle. The impact of ultima ratio on the different sub-decisions of the judicial application of the criminal law is spelt out in the decisions on qualification, evidence (inferences), interpretation and consequences in sentencing. Next, the role of ultima ratio on decisions in appeal and in cassation is analysed. The third part and conclusion deals with the main ideologies of ultima ratio and the wider issue of its role in securing a guarantee oriented criminal law in Europe.